2020
DOI: 10.1039/c9tc04916a
|View full text |Cite
|
Sign up to set email alerts
|

Reduced graphene oxide today

Abstract: A summary of the most important technological applications employing reduced graphene oxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
259
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 505 publications
(266 citation statements)
references
References 255 publications
1
259
0
6
Order By: Relevance
“…Reduced graphene oxide (RGO) has a heterogeneous structure consisting of graphenelike basal plane, which is decorated with additional structural defects and populated with places containing oxidized chemical groups and heteroatoms [233]. It exhibits similar mechanical, conductive and optoelectronic characteristics to pristine graphene.…”
Section: Reduced Graphene Oxide (Rgo)mentioning
confidence: 99%
“…Reduced graphene oxide (RGO) has a heterogeneous structure consisting of graphenelike basal plane, which is decorated with additional structural defects and populated with places containing oxidized chemical groups and heteroatoms [233]. It exhibits similar mechanical, conductive and optoelectronic characteristics to pristine graphene.…”
Section: Reduced Graphene Oxide (Rgo)mentioning
confidence: 99%
“…rGO, as schematically presented in Figure 1 a, has a graphene-like basal plane that is decorated with structural defects during its synthesis and occupied with areas containing oxidizing chemical groups. 9 …”
Section: Introductionmentioning
confidence: 99%
“…It is well demonstrated that bandgap of GO can be tailored by controlling coverage, arrangement and relative ratio of the epoxy and hydroxyl groups [42][43][44]. The similar mechanical, optoelectronic or conductive graphene-like properties of reduced graphene make it highly desirable material to be used in a surfeit of application including catalysis due to its heterogeneous structure comprising graphene-like basal plane additionally decorated with structural defects and occupied with areas containing oxidized chemical groups [45].…”
Section: Introductionmentioning
confidence: 99%